Stress susceptibility in pigs selected for muscling - Wheat, J.D.; Kropf, Donald H.; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Duroc swine selected for muscling seemingly are more susceptible to stress than are ordinary pigs. The highly significant difference in serum creatine phosphokinase (CPK) levels (an average score of 30.07) in those pigs and levels (18.88) in control-line pigs indicates that pigs selected for increased muscling are more susceptible to stress because exercise causes CPK levels to be proportionately higher in their blood serum than would be the case were the pigs not under stress.
Bright Future? is known as Swine Day, 1977
Keywords: Swine; Stress; Muscling; Creatine phosphokinase (CPK)